Mg < 2 + > doped and Li2SeO4 coated LiNiO2 positive electrode material and preparation method thereof

Through Mg2+ doping and Li2SeO4 coated LiNiO2 positive electrode material, the problem of structure/surface degradation of LiNiO2 in lithium-ion batteries is solved, and higher cyclic stability and rate performance are achieved, enhancing structural and interface stability.

CN120565607APending Publication Date: 2025-08-29GUANGXI TECHCAL COLLEGE OF MACHINERY & ELECTRICITY +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510555445.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-29
Publication Date
2025-08-29

AI Technical Summary

Technical Problem

The existing LiNiO2 positive electrode material has poor cycle stability and thermal stability due to structural/surface degradation in lithium-ion batteries, and the improvement of doping or coating alone is limited, so it is impossible to effectively suppress structural phase change and interface side reactions.

Method used

Using the binding strategy of Mg2+ doping and Li2SeO4 coating, the crystal structure is stabilized by Mg2+ doping, and the Li2SeO4 coating stabilizes the interface to form a fast ion conductor, inhibiting side reactions on the electrode surface and promoting Li+ diffusion.

Benefits of technology

The cyclic stability and rate performance of LiNiO2 positive electrode material is significantly improved, the capacity retention rate and lithium ion diffusion rate under high temperature and high pressure conditions are improved, and the structural and interface stability is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005383290510000052
    Figure BDA0005383290510000052
  • Figure BDA0005383290510000061
    Figure BDA0005383290510000061
  • Figure HDA0005383290520000011
    Figure HDA0005383290520000011
Patent Text Reader

Abstract

The invention discloses a Mg < 2 + > doped and Li2SeO4 coated LiNiO2 positive electrode material and a preparation method thereof, and belongs to the technical field of lithium ion battery materials. The preparation method comprises the following steps: uniformly mixing LiOH.H2O, Ni (OH) 2 and Mg (OH) 2, sintering, doping generated LiNiO2 crystals with Mg < 2 + > to form a solid solution, namely Mg < 2 + >-doped LiNiO2; and mixing the Mg < 2 + > doped LiNiO2 and SeO2, calcining the mixture, and coating the surfaces of LiNiO2 particles with the generated Li2SeO4, so as to obtain the Mg < 2 + > doped and Li2SeO4 coated LiNiO2 positive electrode material. The LiNiO2 is subjected to Mg < 2 + > doping and Li2SeO4 coating, the stability of the structure and the interface of the LiNiO2 can be effectively enhanced, the former inhibits phase change by stabilizing a crystal structure, the latter inhibits side reaction by constructing a stable interface, and the two cooperate to stabilize the structure and the interface of the LiNiO2, so that the diffusion of Li < + > is accelerated. The dual-modified LiNiO2 has excellent cycling stability and rate capability, and the capacity of an electrode containing the dual-modified LiNiO2 is 134mAHg <-1 > when the electrode is charged / discharged at 10C; and after 200 cycles at 25 DEG C and 0.5 DEG C and between 2.7 V and 4.3 V, the capacity retention ratio is 90%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-ion battery materials, and specifically relates to a Mg 2+ Doped and Li2SeO4-coated LiNiO2 cathode material and preparation method thereof. Background Art

[0002] Low-cost, high-energy-density lithium-ion batteries (LIBs) have been widely used in energy storage and electric vehicles. Cobalt-free LiNiO2 has a high theoretical capacity (274 mAHg -1 ) and low cost, making it a potential cathode material. However, due to severe structural / surface degradation, LiNiO2 has poor cycling stability and thermal stability, which hinders its application. LiNiO2 structural / surface degradation can be attributed to irreversible phase transitions, cation mixing, residual lithium compounds on the surface, and side reactions at the electrode / electrolyte interface. In order to improve the performance of LiNiO2, two methods have been developed to inhibit structural / surface degradation. The first is doping (such as Na + Mg 2+ 、Al 3+ 、Ga 3+ 、Mn 4+ 、Cu 2+ 、W 6+ 、F - Mg 2+ -Al 3+ Mg 2+ -Cu 2+ Mg 2+ -Mn 4+ etc.) can effectively improve the performance by stabilizing the structure of LiNiO2. The capacity retention rate of 5% Mg-doped LiNiO2 after 100 cycles at 1C is 73%, while the capacity retention rate of pure LiNiO2 is only 57%. Secondly, coating (such as Al2O3, SiO2, V2O5, ZrO2, La2O3, MnCO3, Se, C4H6O4, etc.) has also been used to improve the performance by stabilizing the LiNiO2 interface. However, the improvement of LiNiO2 performance by doping or coating alone is very limited. Doping alone has problems such as the inability to effectively suppress interface side reactions and uneven distribution of doping elements; and although coating alone can protect the surface of the material, it cannot suppress the structural phase transition inside the material (such as the transition from layered to spinel / rock salt phase) and lattice oxygen loss, and the coating layer has poor adaptability to volume changes during charge and discharge. To this end, it is necessary to develop a strategy that combines doping and coating to further improve the performance of LiNiO2. Therefore, synergistic stabilization of structure and interface is a wise choice to improve the performance of LiNiO2.

[0003] Li2SeO4 coated fast ion conductor can effectively improve the interface stability and reduce the Li+ For example, the patent publication number CN 114203993 A discloses a Li2SeO4 fast ion conductor modified lithium ion battery positive electrode material, which uniformly coats Li2SeO4 on the positive electrode material particle interface, which can hinder the electrolyte from corroding the electrode material and improve the long cycle performance and thermal stability of the positive electrode material. However, the SeO3 formed during the coating process 2- / SeO4 2- Doped gradient subsurface SeO 2- It is not enough to stabilize the structure, resulting in limited improvement of LiNiO2. Therefore, the present invention adopts a method of adding Mg 2+ A strategy combining doping and Li2SeO4 coating is proposed to further improve the performance of LiNiO2. Summary of the Invention

[0004] In view of the above problems, the present invention provides a Mg 2-+ Doped and Li2SeO4 coated LiNiO2 cathode material and preparation method thereof, by Mg 2+ Doping and Li2SeO4 coating can effectively enhance the structure and interface stability of LiNiO2. The LiNiO2 modified by Mg-Se synergistically has excellent cycle stability and rate performance.

[0005] The present invention is achieved through the following technical solutions:

[0006] A Mg 2+ LiNiO2 cathode material doped with Li2SeO4, LiOH·H2O, Ni(OH)2 and Mg(OH)2 were uniformly mixed and sintered, Mg 2+ The generated LiNiO2 crystals are doped to form a solid solution, namely Mg 2+ Doped LiNiO2; Mg 2+ Doped LiNiO2 and SeO2 are mixed and calcined, and the generated Li2SeO4 coats the surface of LiNiO2 particles to obtain Mg 2+ Doped and Li2SeO4-coated LiNiO2 cathode material.

[0007] Furthermore, the Mg 2+ The doped and Li2SeO4-coated LiNiO2 cathode material consists of spherical particles with a size of 5 to 20 μm, and a Li2SeO4 coating layer with a thickness of 18 to 22 nm exists on the surface of the particles.

[0008] Furthermore, the Mg 2+ The crystal structure parameters of the LiNiO2 cathode material doped and Li2SeO4 coated are: I (003) / I (104) =1.35~1.40.

[0009] A Mg as described above 2+ The preparation method of the LiNiO2 cathode material doped with Li2SeO4 comprises the following steps:

[0010] (1) Sintering: LiOH·H2O, Ni(OH)2 and Mg(OH)2 were uniformly mixed, and the resulting mixture was sintered once, and then sintered twice in a pure oxygen atmosphere to obtain Mg 2+ Doped LiNiO2;

[0011] (2) Calcination: Mg prepared in step (1) 2+ Doped LiNiO2 and SeO2 were dispersed in anhydrous ethanol, the resulting mixture was stirred, and after removing the ethanol, the resulting powder was calcined in a pure oxygen atmosphere to obtain Mg 2+ Doped and Li2SeO4-coated LiNiO2 cathode material.

[0012] Furthermore, in step (1), the molar ratio of LiOH·H2O, Ni(OH)2 and Mg(OH)2 is 1-1.05:0.95-1.0:0.01.

[0013] Furthermore, in step (1), the primary sintering temperature is 450-500° C., and the sintering time is 10-12 hours.

[0014] Furthermore, in step (1), the secondary sintering temperature is 650-700° C., and the time is 14-16 hours.

[0015] Furthermore, in step (2), the Mg 2+ The mass ratio of doped LiNiO2 and SeO2 is 95-100:1.

[0016] Furthermore, in step (2), the calcination temperature is 300-400° C. and the calcination time is 10-12 hours.

[0017] Furthermore, in step (2), the stirring temperature is 55-60° C. and the stirring time is 3-4 h.

[0018] Mg of the present invention 2+ Preparation principle of doped and Li2SeO4-coated LiNiO2 cathode material:

[0019] The crystal structure of LiNiO2 is layered α-NaFeO2 type (space group: R-3m), in which Li + Occupying the octahedral 3a site, Ni3+ Occupies the 3b site, oxygen forms a densely packed layer. Mg 2+ Ionic radius With Li + Close, so Mg 2+ Can partially occupy Li + The interlayer octahedral sites form a solid solution. Mg 2+ Replace Li + This will lead to a local excess of positive charge, forming Li vacancies, and some Ni 3+ Oxidized to Ni 4+ This charge compensation mechanism makes Mg 2+ Doping is thermodynamically feasible. During the synthesis or subsequent treatment of the positive electrode material, the residual Li on the surface reacts with SeO2 to form Li2SeO4, which is a fast ion conductor. This coating isolates the direct contact between the electrode and the electrolyte, inhibits the side reactions on the electrode surface, and promotes the Li + Therefore, Mg 2+ Doping and Li2SeO4 coating can effectively improve the performance of LiNiO2.

[0020] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0021] 1. The present invention adopts Mg 2+ Doping and Li2SeO4 coating improve the performance of LiNiO2. The former inhibits phase transition by stabilizing the crystal structure, and the latter inhibits side reactions by building a stable interface. The two work together to stabilize the structure and interface of LiNiO2, thereby accelerating Li + During this process, Mg 2+ Partially replace Li + As a pillar, it can improve structural stability and promote Li + At the same time, SeO2 reacts with the residual lithium to form a fast ion conductor Li2SeO4 coated on the surface of LiNiO2. The Li2SeO4 coating not only suppresses the side reactions on the electrode surface, but also promotes the diffusion of Li in the coating. + Therefore, through Mg 2+ Doping and Li2SeO4 coating can effectively enhance the structure and interface stability of LiNiO2.

[0022] 2. Mg of the present invention 2+ The synergistic modification of doping and Li2SeO4 coating can effectively enhance the structural and interfacial stability of LiNiO2. The LiNiO2 modified by Mg-Se has excellent cycle stability and rate performance. When charged / discharged at 10C, the capacity of the electrode containing double-modified LiNiO2 (134mAHg -1) is better than pure LiNiO2 (94mAHg -1 After 200 cycles between 2.7 V and 4.3 V at 25 ° C and 0.5 ° C, the capacity retention rate of the electrode containing double-modified LiNiO2 (90%) is much higher than that of pure LiNiO2 (51%), Se-modified LiNiO2 (64%) and Mg-modified LiNiO2 (64%). 2+ Even after 100 cycles under the harsh conditions of 4.5 V or 55 ° C, the capacity retention rate of the electrode containing double-modified LiNiO2 (83%, 72%) is significantly better than that of pure LiNiO2 (65%, 30%). BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 These are the XRD patterns of Mg-Se-LNO, LNO, Se-LNO, and Mg-LNO prepared in Example 1 and Comparative Examples 1-3, respectively.

[0024] Figure 2 These are SEM images of Mg-Se-LNO, LNO, Se-LNO, and Mg-LNO prepared in Example 1 and Comparative Examples 1-3, respectively.

[0025] Figure 3 TEM image of Mg-Se-LNO prepared in Example 1.

[0026] Figure 4 The XPS images of Mg-Se-LNO and LNO prepared in Example 1 and Comparative Example 1 respectively are as follows:

[0027] Figure 5 These are the performance diagrams of Mg-Se-LNO, LNO, Se-LNO, and Mg-LNO prepared in Example 1 and Comparative Examples 1-3, respectively.

[0028] Figure 6 Graphs showing the lithium ion diffusion coefficients of Mg-Se-LNO and LNO prepared in Example 1 and Comparative Example 1, respectively.

[0029] Figure 7 dQ / dv curves and H1-M and H2-H3 diagrams of Mg-Se-LNO and LNO prepared in Example 1 and Comparative Example 1, respectively.

[0030] Figure 8 2 is the XPS graph of the electrode containing Mg-Se-LNO of Example 1 and LNO of Comparative Example 1 after 200 cycles at 0.5°C.

[0031] Figure 9 2 is the XRD pattern of the electrode containing Mg-Se-LNO of Example 1 and LNO of Comparative Example 1 after 200 cycles at 0.5°C.

[0032] Figure 10 2 is an SEM image of the electrode containing Mg-Se-LNO of Example 1 and LNO of Comparative Example 1 after 200 cycles at 0.5°C.

[0033] Figure 11 2 are EIS graphs of the Mg-Se-LNO electrode of Example 1 and the LNO electrode of Comparative Example 1 under different cycles. DETAILED DESCRIPTION

[0034] The present invention is further described in detail below through examples. These examples are only used to illustrate the present invention and do not limit the scope of protection of the present invention.

[0035] Example 1

[0036] Mg 2+ Preparation of doped and Li2SeO4-coated LiNiO2 cathode materials:

[0037] LiOH·H2O, Ni(OH)2 and Mg(OH)2 were uniformly mixed in a molar ratio of 1.04:0.99:0.01, and the resulting mixture was sintered at 480°C for 10 h and then sintered at 700°C for 15 h in a pure oxygen atmosphere to obtain Mg 2+ Doped LiNiO2 (denoted as Mg-LNO). 2+ Doped LiNiO2 and SeO2 were dispersed in anhydrous ethanol at a mass ratio of 99:1, and the resulting mixture was stirred at 60 ° C for 4 h. After removing the ethanol, the resulting powder was calcined at 350 ° C for 10 h in a pure oxygen atmosphere to obtain Mg 2+ Doped and Li2SeO4-coated LiNiO2 cathode material (denoted as Mg-Se-LNO).

[0038] Example 2

[0039] Mg 2+ Preparation of doped and Li2SeO4-coated LiNiO2 cathode materials:

[0040] LiOH·H2O, Ni(OH)2 and Mg(OH)2 were uniformly mixed in a molar ratio of 1.05:0.95:0.01, and the resulting mixture was sintered at 500℃ for 10h and then sintered at 700℃ for 14h in a pure oxygen atmosphere to obtain Mg 2+ Doped LiNiO2. Mg 2+ Doped LiNiO2 and SeO2 were dispersed in anhydrous ethanol at a mass ratio of 100:1, and the resulting mixture was stirred at 58 ° C for 4 h. After removing the ethanol, the resulting powder was calcined at 400 ° C for 11 h in a pure oxygen atmosphere to obtain Mg 2+Doped and Li2SeO4-coated LiNiO2 cathode material.

[0041] Example 3

[0042] Mg 2+ Preparation of doped and Li2SeO4-coated LiNiO2 cathode materials:

[0043] LiOH·H2O, Ni(OH)2 and Mg(OH)2 were uniformly mixed in a molar ratio of 1.00:1.00:0.01, and the resulting mixture was sintered at 450°C for 12 h and then sintered at 650°C for 16 h in a pure oxygen atmosphere to obtain Mg 2+ Doped LiNiO2. Mg 2+ Doped LiNiO2 and SeO2 were dispersed in anhydrous ethanol at a mass ratio of 95:1, and the resulting mixture was stirred at 55 ° C for 4 h. After removing the ethanol, the resulting powder was calcined at 300 ° C for 12 h in a pure oxygen atmosphere to obtain Mg 2+ Doped and Li2SeO4-coated LiNiO2 cathode material.

[0044] Comparative Example 1

[0045] Preparation of LiNiO2 cathode material:

[0046] LiOH·H2O and Ni(OH)2 were uniformly mixed in a molar ratio of 1.04:0.99, and the resulting mixture was sintered at 480°C for 10 h and then at 700°C for 15 h in a pure oxygen atmosphere to obtain LiNiO2 positive electrode material (denoted as LNO).

[0047] Comparative Example 2

[0048] Preparation of Se-modified LiNiO2 cathode materials:

[0049] LiOH·H2O and Ni(OH)2 were uniformly mixed in a molar ratio of 1.04:0.99, and the resulting mixture was sintered at 480°C for 10 hours, and then sintered at 700°C in a pure oxygen atmosphere for 15 hours to obtain LiNiO2. LiNiO2 and SeO2 were dispersed in anhydrous ethanol at a mass ratio of 99:1, and the resulting mixture was stirred at 60°C for 4 hours. After removing the ethanol, the resulting powder was calcined at 350°C in a pure oxygen atmosphere for 10 hours to obtain Se-modified LiNiO2 positive electrode material (denoted as Se-LNO).

[0050] Comparative Example 3

[0051] Mg 2+ Preparation of doped LiNiO2 cathode material:

[0052] LiOH·H2O, Ni(OH)2 and Mg(OH)2 were uniformly mixed in a molar ratio of 1.04:0.99:0.01, and the resulting mixture was sintered at 480°C for 10 h and then sintered at 700°C for 15 h in a pure oxygen atmosphere to obtain Mg 2+ Doped LiNiO2 (denoted as Mg-LNO).

[0053] Material structure characterization and analysis

[0054] (1) XRD analysis

[0055] The crystal structures of Mg-Se-LNO, LNO, Se-LNO, and Mg-LNO prepared in Example 1 and Comparative Examples 1-3 were characterized by X-ray diffractometer (XRD). Figure 1 and as shown in Table 1. Figure 1 (a) is the XRD pattern of Mg-Se-LNO, LNO, Se-LNO, Mg-LNO, Figure 1 (bc) is the splitting graph of (006) / (102) and (018) / (110), Figure 1 (dg) XRD patterns of LNO, Se-LNO, Mg-LNO and Mg-Se-LNO, respectively.

[0056] Figure 1 The XRD spectra of the four samples of LNO, Se-LNO, Mg-LNO and Mg-Se-LNO can be retrieved to have (PDF#0063) space group of α-NaFeO2 layered structure, and no peaks related to magnesium compounds and selenium compounds were observed. In addition, the apparent splitting of (006) / (102) and (108) / (110) Figure 1 (b-c)) show the well-stratified structures of the four samples.

[0057] In the crystal structure data of the four samples of LNO, Se-LNO, Mg-LNO and Mg-Se-LNO in Table 1, the smaller R wp (<15%) and CHI 2 The increase in lattice parameters (a, c, and V) of Se-LNO samples compared to LNO is due to the incorporation of Se into lattice oxygen, which changes the O 2- The decrease in the lattice parameter of Mg-LNO is due to the small ionic radius of Mg 2+ (0.072nm) occupies Li + (0.076nm). The higher c / a value and I (003) / I (104)This means that its layered structure is more ordered. Mg-LNO has a smaller Li-O interlayer distance (d LiO6 ) and a larger TM-O layer thickness (d TMO6 ), because Li + Mg 2+ And Se-LNO has a larger Li-O interlayer spacing and a smaller TM-O thickness than LNO because SeO3 2- / SeO4 2- Occupy O 2- As a result, Mg-Se-LNO has a larger lithium interlayer spacing and a smaller TM-O thickness than Mg-LNO. In particular, Mg-Se co-modification significantly reduces the Li + / Ni 2+ These results confirm that Mg-Se co-modification can simultaneously enhance the stability of the layer structure and promote the Li + of the spread.

[0058] Table 1 Crystal structures of LNO, Mg-LNO, Se-LNO and Mg-Se-LNO

[0059]

[0060]

[0061] (2) SEM analysis

[0062] The Mg-Se-LNO, LNO, Se-LNO, and Mg-LNO prepared in Example 1 and Comparative Examples 1-3 were characterized and analyzed using scanning electron microscopy (SEM). Figure 2 shown. Figure 2 (ad) are SEM images of LNO, Se-LNO, Mg-LNO and Mg-Se-LNO, respectively; (e) is the EDS image of Mg-Se-LNO; and (f) is the element content diagram of Mg-Se-LNO.

[0063] Depend on Figure 2 (ad) It can be seen that LNO, Se-LNO, Mg-LNO and Mg-Se-LNO are composed of 5-20μm spherical particles. Compared with LNO and Mg-LNO, the particle boundaries of Se-LNO and Mg-Se-LNO samples are tightly bounded and there is no obvious boundary, indicating that Se compounds are coated on the surface of LNO sample particles. The coating of Se compounds on the surface contributes to structural and interfacial stability because it reduces side reactions on the electrode surface and dissolution of metal ions by inhibiting the penetration of electrolyte into the particles. Figure 2(ef) It can be seen that magnesium and selenium are evenly distributed in Mg-Se-LNO.

[0064] (3) TEM analysis

[0065] The Mg-Se-LNO prepared in Example 1 was characterized and analyzed using a transmission electron microscope (TEM). Figure 3 shown. Figure 3 (ab) are TEM images of Mg-Se-LNO at different magnifications. Figure 3 (cd) are the labeled images of region I and region II by HRTEM and FFT.

[0066] Depend on Figure 3 (ab) It can be seen that there is a 20 nm thick coating layer on the surface of Mg-Se-LNO. The lattice fringes with a lattice spacing of 0.47 nm in region I correspond to the (003) crystal plane of LiNiO ( Figure 3 (c)), the spacing of region II is 0.44nm, which corresponds to the Li2SeO4(102) crystal plane ( Figure 3 (d)). Therefore, the coating on the surface of Mg-Se-LNO is Li2SeO4.

[0067] (IV) XPS analysis

[0068] X-ray photoelectron spectroscopy (XPS) was used to characterize the Mg-Se-LNO and LNO prepared in Example 1 and Comparative Example 1, respectively. Figure 4 shown. Figure 4 (a) is the full XPS spectrum of Mg-Se-LNO and LNO. Figure 4 (bd) XPS spectra of Mg-Se-LNO and LNO in Se 3d, Ni 2p, and C 1s regions, respectively.

[0069] Figure 4 In addition to the Ni 2p, O 1s, and C1s peaks in both samples, the characteristic peaks of Se were observed in Mg-Se-LNO ( Figure 4 (a)). Due to the low content of Mg-Se-LNO and the shielding effect of the coating, no characteristic peak of Mg was observed in Mg-Se-LNO. 3d It can be Se 4+ (59.5eV), Se 6+ 3d 5 / 2 (60.5eV) and Se 6+ 3d 3 / 2 (61.6eV)( Figure 4 (b)), corresponding to SeO3 2- / SeO4 2-Near surface doping and Li2SeO4 coating. The peaks at 854.9 and 856.2 eV are related to Ni 2+ and Ni 3+ related( Figure 4 (c)). Mg-Se-LNO Ni 3+ / Ni 2+ The ratio (1.518) is greater than that of LNO (1.465), indicating that the Ni 3+ content, making Li + / Ni 2+ The Li2CO3 peak of Mg-Se-LNO is weakened compared with LNO ( Figure 4 (d)) is mainly due to the fact that the Li2SeO4 coating consumes the residual surface lithium compounds, which helps to reduce the side reactions between the surface lithium compounds and the electrolyte and improve the performance.

[0070] Material performance characterization and analysis

[0071] (1) Cycling stability and rate performance analysis

[0072] The properties of Mg-Se-LNO, LNO, Se-LNO and Mg-LNO prepared in Example 1 and Comparative Examples 1-3 were compared under different conditions. Figure 5 shown. Figure 5 (ac) Initial charge / discharge curves, rate performance, and cycling stability of Mg-Se-LNO, LNO, Se-LNO, and Mg-LNO, respectively.

[0073] Depend on Figure 5 It can be seen that the decrease in the initial capacity of Se-LNO, Mg-LNO and Mg-Se-LNO is due to the Li2SeO4 coating and the inactive Mg 2+ As a result of doping, this reduces the active material content. The capacity of Mg-Se-LNO was 134 mAHg when charged / discharged at 10C. -1 , better than LNO(94mAHg -1 )、Mg-LNO(112mAHg -1 ) and Se-LNO(112mAHg -1 ). After 200 cycles between 2.7V and 4.3V at 25℃ and 0.5℃, the capacity retention of Mg-Se-LNO (90%) is significantly higher than that of LNO (51%), Se-LNO (64%), and Mg-LNO (67%). Even after 100 cycles under the harsh conditions of 4.5V or 55℃, the capacity retention of Mg-Se-LNO (83%, 72%) is much better than that of LNO (65%, 30%). These results show that Li2SeO4 coating and Mg2+ Doping can effectively improve the cycle stability and rate performance of LiNiO2.

[0074] (2) Analysis of lithium ion diffusion coefficient

[0075] The lithium ion diffusion coefficients of Mg-Se-LNO and LNO prepared in Example 1 and Comparative Example 1 were analyzed. GITT studied the lithium ion diffusion coefficients of Li2SeO4 coating and Mg 2 Doping with Li + The impact of diffusion, such as Figure 6 shown. Figure 6 (ab) The charge and discharge curves of Mg-Se-LNO and LNO, respectively.

[0076] Depend on Figure 6 It can be seen that the Li + The diffusion coefficient is much larger than that of LNO, indicating that Li2SeO4 coating and Mg 2+ Doping enhances lithium ion diffusion. In addition to improving rate performance, Li + The rapid diffusion of Li can also reduce the Li + concentration gradient, which helps to reduce strain and suppress capacity fade.

[0077] (3) Phase change analysis

[0078] Phase transition analysis of Mg-Se-LNO and LNO prepared in Example 1 and Comparative Example 1 was performed, and dQ / dV was used to study the Li2SeO4 coating and Mg 2 The effect of doping on phase transition, the results are as follows Figure 7 shown. Figure 7 (ab) dQ / dV curves of LNO and Mg-Se-LNO, respectively. Figure 7 (cd) H1-M and H2-H3 diagrams of LNO and Mg-Se-LNO, respectively.

[0079] The dQ / dV curves of LNO and Mg-Se-LNO samples ( Figure 7 (a, b) consists of three pairs of oxidation / reduction peaks, representing the three-phase transition and Depend on Figure 7 As shown in (ab), the stronger the peak intensity of Mg-Se-LNO, the higher the Li + The faster the kinetic diffusion, the more confirmed that Li2SeO4 coating and Mg 2+ Doping accelerated Li + diffusion. and The potential difference between them gradually increases as the cycle progresses due to the irreversibility of phase change. Figure 7 (c) It can be seen that the ΔV1 of Mg-Se-LNO increases from 0.032V to 0.042V after 100 cycles, while that of LNO increases from 0.056V to 0.080V. Figure 7 (d) It can be seen that for 1 st and 100 tH The ΔV2 of LNO is 0.059V and 0.168V respectively, and that of Mg-Se-LNO is 0.039V and 0.07V respectively. The smaller ΔV1 and ΔV2 of Mg-Se-LNO indicate that Mg 2+ Doping enhances and The reversibility of phase change during the cycle process helps to improve the structural stability and mechanical stability of the material during the cycle process.

[0080] (IV) XPS analysis of the electrode after 200 cycles at 0.5°C

[0081] The interface film (CEI) of the electrodes containing Mg-Se-LNO and LNO of Example 1 and Comparative Example 1 after 200 cycles at 0.5°C was characterized by XPS. Figure 8 shown. Figure 8 (ac) are XPS spectra of electrodes containing Mg-Se-LNO and LNO in the C1s, O1s, and F 1s regions, respectively.

[0082] Figure 8 In (a), CO (286.5 eV), OC=O (289.0 eV) and Li2CO3 (290.1 ​​eV) come from the decomposition products of the electrolyte during the charge and discharge process, while CC (284.7 eV), CH (285.4 eV) and CF (291.2 eV) are related to polyvinylidene fluoride (PVDF) and conductive carbon black. Figure 8 CO (533.5 eV) and C=O (531.9 eV) in (b) represent ether and carbonate, respectively. Figure 8 (c) The peaks at 687.8 eV and 685.3 eV belong to LiPFO, respectively. x The characteristic peaks of LiF and Li2CO3 are derived from the decomposition of LiPF6. x and LiF are the main components of CEI. The contents of CO, OC=O, Li2CO3, LiPFOx, and LiF can be calculated by Figure 8 Calculation of XPS data in. After 200 cycles at 0.5℃, CO, OC=O, Li2CO3, LiPFO xThe LiF content is about 10–20% lower than that of the LNO electrode, which further confirms that Li2SeO4 coating can effectively inhibit the decomposition of the electrolyte on the electrode surface.

[0083] (5) XRD analysis of the electrode after 200 cycles at 0.5°C

[0084] The electrodes containing Mg-Se-LNO and LNO of Example 1 and Comparative Example 1 were characterized by XRD after 200 cycles at 0.5°C. The results are as follows: Figure 9 shown. Figure 9 (a) is the XRD pattern of the electrode containing Mg-Se-LNO and LNO, Figure 9 (b) is the XRD pattern of Li2CO3.

[0085] Figure 9 I in LNO and Mg-Se-LNO (003) / I (004) The values ​​are calculated to be 1.05 and 1.38 respectively. (003) / I (004) Higher, indicating Mg 2+ Doping and Li2SeO4 coating can better alleviate the degradation of the layered structure. Figure 9 (a) It can be seen that due to the decomposition of the electrolyte, characteristic peaks related to Li2CO3 are detected in LNO and Mg-Se-LNO. Figure 9 (b) It can be seen that the weaker Li2CO3-related peak in Mg-Se-LNO means less side reaction between LiNiO2 and electrolyte. Figure 9 The results further showed that Mg 2+ Doping and Li2SeO4 coating can improve the structural and interface stability.

[0086] (5) SEM analysis of the electrode after 200 cycles at 0.5°C

[0087] Focused ion beam scanning electron microscopy (FIB-SEM) was used to observe microcracks in the electrodes containing Mg-Se-LNO of Example 1 and LNO of Comparative Example 1 after 200 cycles at 0.5°C. Figure 10 (a) and (b) SEM images of electrodes containing LNO and Mg-Se-LNO, respectively.

[0088] After 200 cycles, obvious cracks appeared inside the LNO particles ( Figure 10 (a)), while there are only a few microcracks inside the Mg-Se-LNO particles ( Figure 10 (b)). The formation of cracks and The microcracks not only lead to particle crushing, but also provide new contact surfaces, accelerate electrolyte side reactions, and hinder lithium ion diffusion. Therefore, the Mg-Se synergistic modification improves the reversibility of the H2-H3 phase transition, which helps stabilize the structure, inhibit the side reactions of the electrolyte, and enhance the Li + diffusion.

[0089] (6) EIS (electrochemical impedance spectroscopy) analysis of electrodes under different cycles

[0090] The EIS of the electrodes containing Mg-Se-LNO of Example 1 and LNO of Comparative Example 1 were analyzed at different cycles to study the effect of Mg-Se co-modification on electrode kinetics. Figure 11 shown. Figure 11 (ab) is the Nyquist curve, Figure 11 (ce) are R sf 、R ct 、D Li + picture.

[0091] Figure 11 The Nyquist curves in (ab) consist of two half-rings in the mid- and high-frequency regions and a straight line in the low-frequency region, which correspond to the CEI impedance (R sf ), charge transfer resistance (R ct ) and Li in the active material + Diffusion-related Warburg impedance (D Li + ).Depend on Figure 11 (ce) It can be seen that as the cycle progresses, the structure of the electrode surface degrades and the side reactions intensify, resulting in R sf and R ct The increase of D Li + The R of Mg-Se-LNO sf and R ct 70% of LNO and 30%-40% of Mg-Se-LNO Li + About 3 times that of LNO. Rsf and Rct of Mg-Se-LNO are lower, D Li + The higher value is attributed to the Li2SeO4 coating and Mg 2+ Doping enhances structural and interfacial stability.

[0092] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A Mg 2+ Doped and Li2SeO4 coated LiNiO2 cathode material, characterized in that, LiOH·H2O, Ni(OH)2 and Mg(OH)2 are uniformly mixed and sintered. 2+ The generated LiNiO2 crystals are doped to form a solid solution, namely Mg 2+ Doped LiNiO2; then Mg 2+ Doped LiNiO2 and SeO2 are mixed and calcined, and the generated Li2SeO4 coats the surface of LiNiO2 particles to obtain Mg 2+ Doped and Li2SeO4-coated LiNiO2 cathode material.

2. Mg according to claim 1 2+ Doped and Li2SeO4 coated LiNiO2 cathode material, characterized in that, The Mg 2+ The doped and Li2SeO4-coated LiNiO2 cathode material consists of spherical particles with a size of 5 to 20 μm, and a Li2SeO4 coating layer with a thickness of 18 to 22 nm exists on the surface of the particles.

3. Mg according to claim 1 2+ Doped and Li2SeO4 coated LiNiO2 cathode material, characterized in that, The Mg 2+ The crystal structure parameters of the LiNiO2 cathode material doped and Li2SeO4 coated are: I (003) / I (104) =1.35~1.

40.

4. A Mg as described in any one of claims 1 to 3 2+ The method for preparing a LiNiO2 cathode material doped with and coated with Li2SeO4 is characterized in that: The following steps are involved: (1) Sintering: LiOH·H2O, Ni(OH)2 and Mg(OH)2 were uniformly mixed, and the resulting mixture was sintered once, and then sintered twice in a pure oxygen atmosphere to obtain Mg 2+ Doped LiNiO2; (2) Calcination: Mg prepared in step (1) 2+ Doped LiNiO2 and SeO2 were dispersed in anhydrous ethanol, the resulting mixture was stirred, and after removing the ethanol, the resulting powder was calcined in a pure oxygen atmosphere to obtain Mg 2+ Doped and Li2SeO4-coated LiNiO2 cathode material.

5. Mg according to claim 4 2+ The method for preparing a LiNiO2 cathode material doped with and coated with Li2SeO4 is characterized in that: In step (1), the molar ratio of LiOH·H2O, Ni(OH)2 and Mg(OH)2 is 1-1.05:0.95-1.0:0.

01.

6. Mg according to claim 4 2+ The method for preparing a LiNiO2 cathode material doped with and coated with Li2SeO4 is characterized in that: In step (1), the primary sintering temperature is 450-500° C. and the sintering time is 10-12 hours.

7. Mg according to claim 4 2+ The method for preparing a LiNiO2 cathode material doped with and coated with Li2SeO4 is characterized in that: In step (1), the secondary sintering temperature is 650-700° C. and the time is 14-16 hours.

8. Mg according to claim 4 2+ The method for preparing a LiNiO2 cathode material doped with and coated with Li2SeO4 is characterized in that: In step (2), the Mg 2+ The mass ratio of doped LiNiO2 and SeO2 is 95-100:

1.

9. Mg according to claim 4 2+ The method for preparing a LiNiO2 cathode material doped with and coated with Li2SeO4 is characterized in that: In step (2), the calcination temperature is 300-400° C. and the calcination time is 10-12 hours.

10. Mg according to claim 4 2+ The method for preparing a LiNiO2 cathode material doped with and coated with Li2SeO4 is characterized in that: In step (2), the stirring temperature is 55-60° C. and the stirring time is 3-4 h.

Citation Information

Patent Citations

  • Li2SeO4 fast ion conductor modified lithium ion battery positive electrode material

    CN114203993A